Development and validation of a contextual measure of functioning for people living with severe mental disorders in rural Africa - Habtamu, Kassahun (BMC Psychiatry, 2016)
BACKGROUND: Most measures of functioning in people with severe mental disorders (SMD) have been developed in Western societies. Many of the questions in these scales are culture-bound, fail to capture differentiation of tasks by gender and are difficult to adapt to other contexts. The aim of this study was to develop a measure of functioning for people with SMD which is contextually appropriate for a rural African setting. METHODS: A review of existing scales, a qualitative study, free listing and pile sorting exercises, and expert consensus were used to establish a pool of items. Cognitive interviewing guided initial item reduction and refinement. The resulting scale was pilot-tested in people with SMD (n = 200) and their caregivers (n = 200) to inform further item reduction based on psychometric properties. The final Butajira Functioning Scale (BFS) comprised 33 items that were common to both men and women, and an additional eight items for women only, covering the following domains: self-care, work, and family and community participation. Psychometric properties of the finalized BFS were examined in a facility-based sample of 150 people with SMD and their caregivers (n = 150), with longitudinal follow-up of n = 84. RESULTS: The BFS in people with SMD had excellent internal consistency (Cronbach’s α = 0.99), acceptable convergent validity (r = 0.88 with the World Health Organization Disability Assessment Schedule [WHODAS-2.0] and r = 0.32 with the Brief Psychiatric Rating Scale [BPRS-E]) and was sensitive to change following treatment (effect size =0.50). Addition of the items specific to women did not improve the psychometric properties. The caregiver version had similar psychometric properties but higher mean values for each item and better responsiveness to change. Exploratory factor analysis of the BFS provided evidence of construct validity, with four underlying dimensions. CONCLUSIONS: We have developed a measure of functioning for people with SMD in a rural, low income country setting with acceptable psychometric properties. The BFS is easy to administer, sensitive to changes following treatment and has content, construct and convergent validity. The BFS includes domains from existing measures, but has more emphasis on social and occupational domains, which reflects priorities in the setting. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-016-1022-3) contains supplementary material, which is available to authorized users.